Video Snapshots: Creating High-Quality Images from Video Clips - Sunkavalli, Kalyan; Joshi, Neel; Kang, Sing Bing; Cohen, Michael; Pfister, Hanspeter (IEEE Transactions on Visualization and Computer Graphics, 2012)
We describe a unified framework for generating a single high-quality still image (“snapshot”) from a short video clip. Our system allows the user to specify the desired operations for creating the output image, such as super-resolution, noise and blur reduction, and selection of best focus. It also provides a visual summary of activity in the video by incorporating saliency-based objectives in the snapshot formation process. We show examples on a number of different video clips to illustrate the utility and flexibility of our system.